1993
DOI: 10.1080/09670269300650161
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of Rubisco initial and total activities to account for observed rates of photosynthetic carbon dioxide assimilation byScenedesmus ecornis

Abstract: LOUIS LEGENDRE 3 ANDBoth initial and total activity of ribulose-l,5, bisphosphate carboxylase/oxygenase (Rubisco) measured for the green alga Scenedesmus ecornis are affected by the experimental procedure and they are not sufficiently high to account for the rates of ~4C fixation by photosynthesis. The very low fl-carboxylase activities detected (less than 3% of the Rubisco total activity) cannot explain the difference in CO2 fixation. Attempts to obtain possible optimal conditions (pH, duration of activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These degrees of activation might be partly attributable to the instability of this enzyme. In kelp extract, temperature increase or long assay duration resulted in the rapid loss of Rubisco activity, which has been termed "fallover" (Gerard and Driscoll, 1996), and was described for green microalgae (Mouget et al, 1993). We have demonstrated that rbcL gene expression was at its maximum in the orange resting cells (Fig.2), illustrating higher CO 2 fixation potential in the orange and green resting cells.…”
Section: Discussionmentioning
confidence: 90%
“…These degrees of activation might be partly attributable to the instability of this enzyme. In kelp extract, temperature increase or long assay duration resulted in the rapid loss of Rubisco activity, which has been termed "fallover" (Gerard and Driscoll, 1996), and was described for green microalgae (Mouget et al, 1993). We have demonstrated that rbcL gene expression was at its maximum in the orange resting cells (Fig.2), illustrating higher CO 2 fixation potential in the orange and green resting cells.…”
Section: Discussionmentioning
confidence: 90%
“…This rapid loss of carboxylase activity may well account for the 100-fold discrepancy between RuBPdependent COs fixation and the photosynthetic rate measured by oxygen evolution. It is well recognized that the measured concentration of Rubisco in algae does not explain the rate of photosynthesis, but there is usually no more than a 2or 3-fold difference (Mouget et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments, the growth response of several microalgal and cyanobacterial species to bacteria was first examined on solid culture media using agar plate methods developed previously [14]. All subsequent experiments using liquid media were conducted with the green microalga S. bicellularis that was rendered axenic by serial transfers on solid medium [17]. The effect of bacteria or a bacterial culture supematant on the growth of microalgae was evaluated in liquid culture as follows: an axenic stock culture of S. bicellularis (cell density, ca.…”
Section: Effect Of Bacteria On the Growth Of Algaementioning
confidence: 99%